(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
According to a number of authors, cholecystitis is one of the most common diseases of the gallbladder and is characterized by inflammation of the walls of the gallbladder with the formation of gallstones in its lumen. According to modern epidemiological data, cholecystitis affects from 17 to 20% of the adult population of the planet, mainly women. The inflammation and destruction of the walls of the gallbladder observed against the background of cholecystitis leads to a gradual loss of the normal function of this organ and disruption of the digestive process [1]. Acute cholecystitis makes up a significant proportion of surgical diseases of the abdominal organs, second only to appendicitis in frequency. In elderly patients, destructive cholecystitis is the main disease in emergency abdominal surgery. Destructive forms of acute cholecystitis occur in 70% of cases. The prevalence of cholelithiasis (GSD) is steadily growing and occupies a leading position among pathologies requiring surgical treatment. Currently, due to the widespread introduction of the ultrasound research method into practical activities, new opportunities have emerged for objective assessment of the degree of inflammatory changes in the wall of the gallbladder and perivesical space. The use of ultrasound techniques should be carried out in all patients with suspected acute cholecystitis, regardless of the severity of clinical symptoms. Thus, in practical surgery there is an urgent need to study the issues of ultrasound diagnosis of acute calculous cholecystitis, develop echosemiotics of each of its forms, and determine the presence of purulent complications.